THE LANGUAGE ATTITUDE OF JABA SPEAKERS IN BALINESE SPEECH COMMUNITY OF SINGARAJA CITY - Ramendra, Dewa Putu (e-Journal of Linguistics, 2015)
This study aims to describe the language attitude of jaba speakers in Balinese speech community of Singaraja city toward Balinese speech levels. To achieve that goal, this research applies mixed method that combines survey and interview method so that the data obtained are of two kinds, that is, quantitative and qualitative data. The samples are grouped into 12 groups based on the variable of occupation, age, and gender, and each group consists of 14 people. Besides, one representative from each group is chosen as language informant to be interviewed. The result of this study shows that the speakers’ attitude toward Balinese speech levels tend to be uniform regardless of the differences in occupation, age, and gender. In this case, the attitude toward alus ‘refined’ and biasa ‘neutral’ is categorized as positive, while the attitude toward kasar ’coarse’ is categorized as neutral. This type of attitude actually shows that jaba speaker like Balinese speeh levels and that Balinese language appears to be in good health. Furthermore, the results of this study also reveal that the attitudes toward Balinese speech levels decreased regularly from the cognitive component to the conative component. The factor responsible for the decline is the presence of Indonesian that has become a heavy competitor for the presence of Balinese language.
Keywords: Langauage, component, and attitudes